2015
DOI: 10.1002/elan.201400578
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Label‐Free Monitoring of Shewanella oneidensis MR‐1 Biofilm Formation on Electrode During Bacterial Electrogenesis Using Scanning Electrochemical Microscopy

Abstract: Formation of biofilm on an electrode surface is usually a prerequisite for efficient electron transfer from electrogenic bacteria onto electrode, and the geometric status of the biofilm governs the generated current. In this study, we propose a real‐time characterization method to track the dynamic formation process of biofilm on electrode using scanning electrochemical microscopy (SECM). Shewanella oneidensis MR‐1 was chosen in this work as an electrogenic model species. A plane electrode at the bottom of a e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The constant-height mode SECM measurements of the patterned cells enabled mapping of the activity of ATP-binding cassette transporters . SECM was applied for real-time characterization of the dynamic formation process of a biofilm of Shewanella oneidensis MR-1 on an electrode by monitoring the redox mediator current of Ru­(NH 3 ) 6 Cl 3 …”
Section: Scanning Electrochemical Microscopymentioning
confidence: 99%
“…The constant-height mode SECM measurements of the patterned cells enabled mapping of the activity of ATP-binding cassette transporters . SECM was applied for real-time characterization of the dynamic formation process of a biofilm of Shewanella oneidensis MR-1 on an electrode by monitoring the redox mediator current of Ru­(NH 3 ) 6 Cl 3 …”
Section: Scanning Electrochemical Microscopymentioning
confidence: 99%
“…Hsing et al reported a dynamic formation process of S. oneidensis biofilms on electrodes using SECM. [24] Figure 4a showed the SECM area scan results presenting a 3D configure corresponding to the edge of biofilm. They also compared the time-lapse approach curves after 2 hr, 25 hr, and 35 hr of the electrogenic experiment, which indicated that the growing bacterial film hindered electron transfer and led to a current decrease.…”
Section: Shewanellamentioning
confidence: 99%
“…Though most of the work dealt with inspections of eukaryotic cells from vertebrates as the more common biological model case, bio-SECM on fungal eukaryotic cells and bacterial prokaryotic cells has been carried out as well. In the context of the development of biofuel cells, the transmembrane charge transfer ability of eukaryotic yeast cells was, for instance, assessed by means of G/C SECM [65,66] colonies [67], quorum sensing of aggregates of Pseudomonas aeruginosa [68] and metabolite production of Pseudomonas aeruginosa during proliferation [69] are examples of G/C-SECM studies with bacterial prokaryotes. Exotic targets for biological SECM studies were salt glands on the leaf of the halophyte Cynodon dactylon (L.) [70] and chloroplasts and their thylakoid membranes for which local photosynthetic flux measurements have been attempted [71].…”
Section: Scanning Electrochemical Microscopy-based Live Cell Imaging: Examples Of Accomplishments From 2012 To Datementioning
confidence: 99%